Mechanical Ventilation in the Critically Ill Obese Patient (Springer International Publishing, 2018)
This book is the first to describe a practical evidence-based approach to the management of critically ill obese patients with various medical or postoperative respiratory problems in the intensive care unit. In brief, the book aims to identify the best strategy and present clinical recommendations for different circumstances, to establish indications for and contraindications to noninvasive and invasive mechanical ventilation, and to offer clear guidance on weaning from mechanical ventilation and on respiratory care. Causes of acute respiratory failure in the obese patient are discussed, and advice is offered on the prevention and management of complications during mechanical ventilation and on moving and feeding critically ill obese patients. Long-term outcomes, ethical issues, and health care costs are also addressed. The multidisciplinary approach, with contributions from international experts in different specialties, ensures that the book will be of interest to a range of health professionals involved in critical care, including intensivists, anesthesiologists, and pulmonologists.